Public investment and the EU fiscal framework - Turrini, Alessandro 1966-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
It is often claimed that the introduction of the EU rules-based fiscal framework of the Maastricht Treaty and the Stability and Growth Pact was responsible for a decline in public investment shares in EU countries. Proposals have also been made in recent times in favour of a revision of the EU fiscal framework in such a way to grant special treatment to public capital expenditures (e.g., by amending it with a 'golden rule'). This paper analyses empirically the relation between the introduction of the EU fiscal framework and public investment. Results from panel data analysis suggest that the impact of the EU rules for fiscal discipline is not a clear-cut one. On the one hand, after phase II of EMU, public investment is found to be more negatively affected by debt levels. This is consistent with the view that in the run-up to Maastricht the budgetary adjustment implied a significant decline in public investment, especially in high-debt countries. On the other hand, results indicate that after phase II of EMU public investment became positively related to previous period budget balances, so that the improvement in the budget balances consequent to the introduction of the EU fiscal rules may have helped to create room for public investment in several EU countries.
Economic Papers